2020
DOI: 10.1063/1.5138238
|View full text |Cite
|
Sign up to set email alerts
|

Groups, Jacobi functions, and rigged Hilbert spaces

Abstract: This paper is a contribution to the study of the relations between special functions, Lie algebras and rigged Hilbert spaces. The discrete indices and continuous variables of special functions are in correspondence with the representations of their algebra of symmetry, that induce discrete and continuous bases coexisting on a rigged Hilbert space supporting the representation. Meaningful operators are shown to be continuous on the spaces of test vectors and its dual. Here, the chosen special functions, called … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Although the formalism of rigged Hilbert spaces is not new as was introduced by Gelfand [7], it has acquired more and more importance by mathematical physicists [8][9][10][11][12][13] and more recently by mathematicians [14][15][16][17][18][19][20]. Furthermore, the authors have published a series of papers in which it is shown the close connection between Lie algebras, special functions, discrete and continuous basis and rigged Hilbert spaces [22][23][24][25][26]. Somehow, the present paper could be included in this collection.…”
Section: Introductionmentioning
confidence: 84%
“…Although the formalism of rigged Hilbert spaces is not new as was introduced by Gelfand [7], it has acquired more and more importance by mathematical physicists [8][9][10][11][12][13] and more recently by mathematicians [14][15][16][17][18][19][20]. Furthermore, the authors have published a series of papers in which it is shown the close connection between Lie algebras, special functions, discrete and continuous basis and rigged Hilbert spaces [22][23][24][25][26]. Somehow, the present paper could be included in this collection.…”
Section: Introductionmentioning
confidence: 84%
“…Jacobi polynomials yield to the main concept of this section, the algebraic Jacobi functions [66,71], defined as…”
Section: Algebraic Jacobi Functionsmentioning
confidence: 99%
“…Then, if we choose |g = |j, m and omit the arbitrary |f ∈ Φ I,H , we have the converse relation to (71) as…”
Section: Associated Laguerre Functions On the Planementioning
confidence: 99%
See 1 more Smart Citation
“…In a series of previous articles [21][22][23][24][25], we have discussed the relations between discrete and continuous basis, algebras of operators, special functions and rigged Hilbert spaces (also called Gelfand triplets). We have shown that all these concepts properly convive in the framework of rigged Hilbert spaces and not on Hilbert spaces.…”
Section: Introductionmentioning
confidence: 99%